Synthesis and In Vitro Cytotoxicity of the 4-(Halogenoanilino)-6-bromoquinazolines and Their 6-(4-Fluorophenyl) Substituted Derivatives as Potential Inhibitors of Epidermal Growth Factor Receptor Tyrosine Kinase - Malose Jack Mphahlele; Hugues K. Paumo; Yee Siew Choong (MDPI AG, 2017)
Series of the 2-unsubstituted and 2-(4-chlorophenyl)-substituted 4-anilino-6-bromoquinazolines and their 6-(4-fluorophenyl)-substituted derivatives were evaluated for in vitro cytotoxicity against MCF-7 and HeLa cells. The 2-unsubstituted 4-anilino-6-bromoquinazolines lacked activity, whereas most of their 2-(4-chlorophenyl) substituted derivatives were found to exhibit significant cytotoxicity and selectivity against HeLa cells. Replacement of bromine with 4-fluorophenyl group for the 2-unsubstituted 4-anilinoquinazolines resulted in superior activity against HeLa cells compared to Gefitinib. The presence of a 4-fluorophenyl group in the 2-(4-chlorophenyl) substituted derivatives led to increased cytotoxicity against HeLa cells, except for the 3-chloroanilino derivative. The most active compounds, namely, 3g, 3l, and 4l, were found to exhibit a moderate to significant inhibitory effect against epidermal growth factor receptor tyrosine kinase (EGFR-TK). The EGFR molecular docking model suggested that these compounds are nicely bound to the region of EGFR.